JUNIOR HIGH SCHOOL STUDENTS’ EXPERIENCES IN GOOGLE CLASSROOM TO PROMOTE AUTONOMY IN ONLINE ENGLISH LEARNING - Aulia Putri Yulistia; Wiwiet Eva Savitri (Eltin Journal : Journal of English Language Teaching in Indonesia, 2022)
Online learning in Education has been increasingly implemented since the pandemic happened. Junior high schools use Google Classroom because it is the potential to enhance the teaching-learning activities, and the students also inevitably have to use it for learning, specifically English subjects. Previous studies claimed that Google Classroom is a useful online learning platform for students and teachers. Learning English online using Google Classroom for reading, writing, and grammar skills is possible. However, the previous studies mainly focused on upper secondary school students and teachers. Hence, thisstudy aims to explore junior high school students’ experiences and learning autonomy in learning English online through Google Classroom during the new regulation of limited face-to-face classes. This study used a qualitative methodology and collected the data through questionnaires and semi-structured interviews. The findings indicated that 7th-grade students with a total of 82 students have positive as well as unpleasant experiences when learning English using Google Classroom. Furthermore, the findings also indicated that junior high school students as reactive autonomous learners could enhance their English learning autonomy when using Google Classroom